The effect of neutrophil-lymphocyte ratio and thrombocyte index on inflammation in patients with periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome - Vildan Gungorer; Alaaddin Yorulmaz; Husamettin Vatansev; Sukru Arslan (Indian Journal of Rheumatology)
Background: The periodic fever, aphthous stomatitis, pharyngitis, and adenitis (PFAPA) syndrome is the most common periodic fever syndrome in childhood. Its pathogenesis and etiology remain unknown. This study aimed to determine whether or not the neutrophil-to-absolute lymphocyte ratio (NLR) and thrombocyte indices could be used as subclinical inflammation markers in healthy control group children and children with PFAPA syndrome during the attacks and attack-free periods. Materials and Methods: Twenty-eight children with PFAPA syndrome that presented to our clinic were enrolled in this study. As a control group, healthy children that presented to the general pediatrics polyclinic with the exact same age and sex as the patient group were recruited. The medical records of all participants were evaluated retrospectively. Results: The leukocyte and neutrophil counts, NLRs, platelet count-to-absolute lymphocyte ratios (PLRs), and C-reactive protein levels of the patients with PFAPA syndrome during the attack period were found to be significantly higher than during the attack-free period. Similarly, during the attack period, the leukocyte and neutrophil counts, NLRs, and PLRs were significantly higher compared to the healthy control group. Patients with PFAPA syndrome during the attack-free periods were compared with the control group, and their mean platelet volume (MPV) values were significantly lower than the control group. Conclusions: MPV in PFAPA syndrome patients was significantly lower during the inflammation. We observed a significant decrease in MPV values during the attack-free period compared to the control group, suggesting that subclinical inflammation continues in the attack-free period in PFAPA syndrome.